A preparation method of a GDC solid electrolyte block, a GDC solid electrolyte block and a low-temperature working GDC-based oxygen sensor
Patent Information
- Application Number
- CN202611022290.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-10-20
AI Technical Summary
[0006]本发明的第一个目的是提供一种具有取向纳米纤维堆积结构的GDC固体电解质块体制备方法,该方法所制备的GDC固体电解质块体能根本性解决在400℃工作温度GDC固体电解质与电极间的界面电阻过大问题,使得基于该固定体电解质构建的氧气传感器在400℃工作温度仍能稳定输出与理论值相符的电势信号
(1)本制备方法所制备出的GDC固体电解质块体质量稳定可靠,通过静电纺丝与纤维取向交叉层叠压烧工艺相结合,使GDC固体电解质块体的内部形成由纳米纤维沿特定取向堆积排列、晶粒沿纤维轴向定向生长的微结构。这种微结构,一方面,不仅提高了块体的尺寸稳定性和结构均匀性,而且为电极/GDC界面提供了数量远超常规的限制性三维反应活性位点,极大地降低了界面氧电荷转移电阻,使得在400℃工作温度,电极反应仍能顺畅进行;另一方面,在GDC电解质体相内构建了更有利于氧离子快速传输的取向路径,降低了晶界对离子传输的总阻力。两种效应协同作用,大大降低了400℃低温下GDC固体电解质与电极间的界面电阻,首次实现了基于该GDC固体电解质块体构建的电位型氧气传感器在400℃仍能准确获得稳定且符合能斯特方程的氧传感响应,将电位型氧气传感器正常工作时的下限温度向下拓展了至少100℃,并且仍有进一步降低的潜力,更适用于汽车尾气、工业锅炉及环境气体监测等领域。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of gas sensor technology, specifically relating to a GDC solid electrolyte block with an oriented nanofiber stacking structure, a method for preparing the GDC solid electrolyte block, and a low-temperature operating GDC base potential oxygen sensor made from the GDC solid electrolyte block. Background Technology
[0002] Oxygen sensors play an irreplaceable role in fields such as automotive exhaust monitoring, industrial boiler combustion control, and environmental gas monitoring. Among them, the concentration cell (potential type) oxygen sensor technology based on yttrium-stabilized zirconia (YSZ) is the most mature. Its core structure typically includes a solid electrolyte matrix made of YSZ, with porous platinum electrodes disposed on both sides of the solid electrolyte. One electrode serves as a reference electrode exposed to a reference atmosphere (such as air) with a known oxygen concentration, while the other electrode serves as the working electrode exposed to the atmosphere to be measured. When the oxygen partial pressures on both sides of the solid electrolyte are different, oxygen ions migrate in the electrolyte at high temperatures, generating a potential difference between the two electrodes. The relationship between this potential difference and the oxygen concentration follows the Nernst equation. However, its operating temperature is usually above 700℃, requiring the integration of a high-power heater, resulting in high sensor power consumption, complex structure, and limiting its application in certain flammable and explosive environments.
[0003] To lower the operating temperature, researchers have attempted to use solid electrolyte materials with higher ionic conductivity. Gadolinium-doped cerium oxide (GDC), due to its significantly higher oxygen ion conductivity than YSZ in the mid-to-low temperature range (500–700 °C), is considered one of the most promising mid-to-low temperature solid electrolytes. However, a long-standing technical bottleneck is that the lower limit of normal operation for GDC bulk ceramics prepared using conventional solid-state methods and other processes, after being actually fabricated into oxygen sensors, is typically still above 500 °C. When the temperature is further reduced to below 450 °C, the output electromotive force of these sensors deviates significantly from the Nernst theoretical value, and may even completely lose its ability to respond to oxygen concentration.
[0004] The root cause of this phenomenon lies in the fact that at low temperatures, the bulk conductivity of the GDC electrolyte decreases, and the kinetics of oxygen ion charge transfer at the electrode interface become extremely slow, resulting in a huge interfacial resistance. This interfacial resistance is directly related to the sensor's output impedance, making it difficult to establish a stable open-circuit potential, and the sensor's output potential is overwhelmed by various noises. Existing technologies attempt to circumvent this problem by fabricating thin-film electrolytes or using hybrid potential structures, but these processes are complex and costly, and hybrid potential sensors are sensitive to interfering gases and have poor selectivity.
[0005] Furthermore, traditional oxygen sensors typically employ an electrochemical pump oxygen circuit to establish a stable reference oxygen partial pressure, which requires additional control circuitry. Therefore, a simpler reference method is also a crucial requirement for the practical application of low-temperature potential-type oxygen sensors. Summary of the Invention
[0006] The first objective of this invention is to provide a method for preparing a GDC solid electrolyte bulk with an oriented nanofiber stacking structure. The GDC solid electrolyte bulk prepared by this method can fundamentally solve the problem of excessive interfacial resistance between the GDC solid electrolyte and the electrode at an operating temperature of 400°C, so that the oxygen sensor constructed based on this stationary electrolyte can still stably output a potential signal that matches the theoretical value at an operating temperature of 400°C.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: a method for preparing a GDC solid electrolyte bulk material with an oriented nanofiber stacking structure, comprising the following steps: (1) Weigh out cerium source and gadolinium source according to Gd doping molar fraction of 20% to 30%, and dissolve them together in an organic solvent. Then add citric acid and polyvinylpyrrolidone (PVP) in sequence and stir thoroughly to obtain a homogeneous spinning solution. (2) Using electrospinning process, the homogeneous spinning solution is electrospun onto the roller of the roller collector to obtain the precursor nanofiber membrane; (3) The precursor nanofiber membrane is laid flat and pre-sintered at 200-300℃ to obtain a flat fiber sheet. Then the fiber sheet is sintered at 500-700℃ to obtain GDC nanofiber sheet. (4) Cut the GDC nanofiber sheet into several small pieces, stack these small pieces in a cross-fiber orientation and press them into a mold to obtain a blank; then sinter the blank after demolding at 500-700℃ to obtain a GDC solid electrolyte block with an oriented nanofiber stacking structure.
[0008] Furthermore, in the aforementioned method for preparing a GDC solid electrolyte block with an oriented nanofiber stacking structure, in step (1), a cerium source and a gadolinium source are weighed according to a Gd doping molar fraction of 20%.
[0009] Furthermore, in the aforementioned method for preparing a GDC solid electrolyte block with an oriented nanofiber stacking structure, in step (1), the cerium source is cerium oxide and the gadolinium source is gadolinium oxide.
[0010] Furthermore, in the aforementioned method for preparing a GDC solid electrolyte block with an oriented nanofiber stacking structure, in step (1), the amount of organic solvent used is: based on the total mass of the cerium source and gadolinium source, 10-20 mL of organic solvent is added per gram of total mass.
[0011] Furthermore, in the aforementioned method for preparing a GDC solid electrolyte block with an oriented nanofiber stacking structure, in step (1), the amount of organic solvent used is: based on the total mass of the cerium source and gadolinium source, 13-15 mL of organic solvent is added per gram of total mass.
[0012] Furthermore, in the aforementioned method for preparing a GDC solid electrolyte bulk material with an oriented nanofiber stacking structure, the organic solvent is N,N-dimethylformamide (DMF).
[0013] Furthermore, in the aforementioned method for preparing a GDC solid electrolyte block with an oriented nanofiber stacking structure, in step (1), the molar ratio of citric acid to the total amount of metal ions is (0.5-2):1, and the total amount of metal ions is the sum of the amounts of cerium ions and gadolinium ions.
[0014] Furthermore, in the aforementioned method for preparing a GDC solid electrolyte block with an oriented nanofiber stacking structure, in step (1), the molar ratio of citric acid to the total amount of metal ions is (0.8-1.2):1, and the metal ions are the sum of cerium ions and gadolinium ions.
[0015] Furthermore, in the aforementioned method for preparing a GDC solid electrolyte block with an oriented nanofiber stacking structure, in step (1), polyvinylpyrrolidone (PVP) with a weight-average molecular weight of 1 to 2 M is selected, and the amount of PVP added accounts for 8% to 15% of the total mass of the homogeneous spinning solution.
[0016] Furthermore, in the aforementioned method for preparing a GDC solid electrolyte block with an oriented nanofiber stacking structure, in step (1), polyvinylpyrrolidone (PVP) with a weight-average molecular weight of 1.3M is selected, and the amount of PVP added accounts for 10% of the total mass of the homogeneous spinning solution.
[0017] Furthermore, in the aforementioned method for preparing a GDC solid electrolyte block with an oriented nanofiber stacked structure, in step (2), the electrospinning process is as follows: the homogeneous spinning solution is transferred to an electrospinning device and collected using a roller collector. During the electrospinning process, the applied DC voltage is 10-20kV, the distance between the needle and the roller collector is 10-20cm, the spinning solution supply rate is 0.5-2.0mL / h, and the roller of the roller collector rotates at a speed of 1000-5000rpm. The roller collector is used to apply circumferential stretching and directional alignment to the deposited fibers to obtain a precursor nanofiber membrane.
[0018] Furthermore, in the aforementioned method for preparing a GDC solid electrolyte block with an oriented nanofiber stacked structure, in step (2), before electrospinning, a release substrate is pre-laid on the surface of the roller collector; during the electrospinning process, the applied DC voltage is 14-16kV, the distance between the needle and the collector is 14-16cm, the spinning solution supply rate is 1.0-1.5mL / h, and the rotation speed of the roller collector is 2500-3500rpm.
[0019] Furthermore, in the aforementioned method for preparing a GDC solid electrolyte block with an oriented nanofiber stacking structure, in step (3), after the precursor nanofiber membrane is laid flat, several air-permeable weights that prevent the fiber membrane from curling are placed at intervals on the surface of the precursor nanofiber membrane, and the precursor nanofiber membrane is pre-sintered at a temperature of 200-300°C for 4-8 hours in an air atmosphere, so that the fiber membrane completes preliminary degreasing and pre-oxidative shrinkage to obtain a flat fiber sheet; Next, the heavy object is removed, the fiber sheet is transferred to a flat firing plate, and a breathable plate is pressed on the surface of the fiber sheet. The temperature is raised to 500-700°C at a rate of 3-10°C / min and held for 30-120 minutes to completely decompose the residual organic matter and form the GDC fluorite phase. After cooling, brittle GDC nanofiber sheets are obtained.
[0020] Furthermore, in the aforementioned method for preparing a GDC solid electrolyte block with an oriented nanofiber stacking structure, in step (3), the pre-sintering temperature in an air atmosphere is 250°C and the treatment time is 6h; the final temperature of the heating after the fiber sheet is transferred to the sintering plate is 600°C, the heating rate is 3~10°C / min, and the holding time is 60min.
[0021] Furthermore, in the aforementioned method for preparing a GDC solid electrolyte block with an oriented nanofiber stacked structure, in step (4), the GDC nanofiber sheet is cut into several small pieces, and these small pieces are stacked in a fiber-oriented cross-laminated manner and placed in a pressing mold. An axial pressure of 1 to 5 MPa is applied to the stacked sheet at room temperature to densify and embed the stacked sheet to obtain a blank. Next, the demolded blank is heated from room temperature to 500-700℃ at a heating rate of 3-10℃ / min and held for 20-60min for sintering strengthening to obtain a GDC solid electrolyte block with an oriented nanofiber stacking structure.
[0022] Furthermore, in the aforementioned method for preparing a GDC solid electrolyte block with an oriented nanofiber stacked structure, in step (4), the axial pressure applied to the stacked sheets during the blanking process using a pressing mold is 2 MPa; and after the blank is demolded, it is heated from room temperature to 600°C at a heating rate of 3-10°C / min and held at that temperature for 30 min for sintering strengthening.
[0023] The second objective of this invention is to provide a GDC solid electrolyte block with an oriented nanofiber stacking structure. This GDC solid electrolyte block can fundamentally solve the problem of excessive interfacial resistance between the GDC solid electrolyte and the electrode at an operating temperature of 400°C, so that the oxygen sensor constructed based on this solid electrolyte block can still stably output a potential signal that matches the theoretical value at an operating temperature of 400°C.
[0024] To achieve the above objectives, the present invention adopts the following technical solution: a GDC solid electrolyte block, wherein the GDC solid electrolyte block is a GDC solid electrolyte block with an oriented nanofiber stacking structure.
[0025] The third objective of this invention is to provide a potential-type oxygen sensor. This sensor employs a GDC solid electrolyte block with an oriented nanofiber stacked structure, and porous platinum electrodes are respectively disposed on both sides of the solid electrolyte block. One electrode serves as a reference electrode exposed to a reference atmosphere with a known oxygen concentration, while the other electrode serves as a working electrode exposed to the atmosphere to be measured. This sensor can fundamentally solve the problem of excessive interfacial resistance between the GDC solid electrolyte and the electrodes at a working temperature of 400°C. It can still stably output a potential signal that matches the theoretical value at a working temperature of 400°C, achieving stable, sensitive, and accurate oxygen detection.
[0026] To achieve the above objectives, the present invention adopts the following technical solution: a low-temperature operating GDC-based oxygen sensor, comprising: GDC solid electrolyte bulk material, wherein the GDC solid electrolyte bulk material is prepared by the preparation method of any one of claims 1 to 16 and has an oriented nanofiber stacking structure, wherein the GDC solid electrolyte bulk material has an opposing upper surface and a lower surface; A first porous platinum electrode is disposed on the lower surface of the GDC solid electrolyte block; A second porous platinum electrode is disposed on the upper surface of the GDC solid electrolyte block; The first lead wire is used to lead out the potential signal of the first porous platinum electrode; The second lead wire is used to extract the potential signal of the second porous platinum electrode.
[0027] Furthermore, the aforementioned cryogenic GDC-based oxygen sensor includes: A GDC solid electrolyte block having an oriented nanofiber stacking structure, the GDC solid electrolyte block having opposing upper and lower surfaces; A first porous platinum electrode is disposed on the lower surface of the GDC solid electrolyte block; A second porous platinum electrode is disposed on the upper surface of the GDC solid electrolyte block; The LSM internal reference block is disposed on the upper surface of the second porous platinum electrode; A platinum current collector layer is disposed on the upper surface of the LSM internal reference block; A glass sealing layer covers all sides of the GDC solid electrolyte block, all seams between the side of the GDC solid electrolyte block and the side of the second porous platinum electrode, all sides of the second porous platinum electrode, all seams between the side of the second porous platinum electrode and the side of the LSM internal reference block, and all sides of the LSM internal reference block. The sealed reference cavity is formed by the GDC solid electrolyte block, the LSM internal reference block, and the glass sealing layer, and the second porous platinum electrode is located inside the sealed reference cavity; The first lead wire is connected to the first porous platinum electrode through conductive silver paste and is used to extract the potential signal of the first porous platinum electrode. The second lead wire is connected to the platinum current collector layer via conductive silver paste and is used to extract the potential signal of the second porous platinum electrode.
[0028] Furthermore, in the aforementioned low-temperature operating GDC-based oxygen sensor, the LSM internal reference block is prepared by weighing a predetermined amount of LSM powder and placing it in a pressing mold, pressing it under a pressure of 1-5 MPa, sintering the molded body at 1300-1500℃ for 8-12 hours to complete solid-state sintering and obtain a dense LSM internal reference block.
[0029] Furthermore, in the aforementioned cryogenic GDC-based oxygen sensor: The first porous platinum electrode is formed by sintering and solidifying a porous platinum electrode slurry coated on the lower surface of the GDC solid electrolyte block at 850-900℃. The second porous platinum electrode is formed by sintering and curing a porous platinum electrode slurry that bonds the upper surface of the GDC solid electrolyte block to the lower surface of the LSM internal reference block at 850-900℃. The platinum current collector layer is formed by sintering and curing a porous platinum electrode paste coated on the upper surface of the LSM internal reference block at 850–900℃. The glass sealing layer is formed by coating a glass slurry made of low-melting-point glass powder and organic solvent, which is then melted at 800-900℃ and cooled to solidify.
[0030] The beneficial effects of implementing the above technical solution are as follows: (I) Beneficial effects of the GDC solid electrolyte bulk preparation method (1) The GDC solid electrolyte bulk prepared by this method has stable and reliable quality. By combining electrospinning with fiber orientation cross-lamination and sintering process, a microstructure is formed inside the GDC solid electrolyte bulk, in which nanofibers are stacked and arranged in a specific orientation and grains are oriented along the fiber axis. This microstructure not only improves the dimensional stability and structural uniformity of the bulk, but also provides a number of restricted three-dimensional reactive sites for the electrode / GDC interface that far exceed the conventional ones, greatly reducing the oxygen charge transfer resistance at the interface, so that the electrode reaction can still proceed smoothly at the working temperature of 400℃; on the other hand, it constructs an orientation path that is more conducive to the rapid transport of oxygen ions in the GDC electrolyte bulk phase, reducing the total resistance of grain boundaries to ion transport. The synergistic effect of the two effects significantly reduces the interfacial resistance between the GDC solid electrolyte and the electrode at a low temperature of 400℃. For the first time, a potential-type oxygen sensor constructed based on this GDC solid electrolyte block can still accurately obtain a stable oxygen sensing response that conforms to the Nernst equation at 400℃. This extends the lower limit temperature for normal operation of the potential-type oxygen sensor by at least 100℃, and there is still potential for further reduction. It is more suitable for fields such as automobile exhaust, industrial boilers and environmental gas monitoring.
[0031] (2) The preparation method is simple and the manufacturing cost is relatively low. It can be achieved by using electrospinning equipment and pressing equipment, without the need for complex and expensive deposition equipment. At the same time, the preparation method has good process compatibility and is easy to connect with existing ceramic sensor production lines, and has high industrial promotion value.
[0032] (3) This preparation method regulates the rheological properties of the spinning solution by using a two-component system of citric acid as a complexing agent and polyvinylpyrrolidone (PVP) as a spinning carrier. Combined with the high-speed rotation of the roller collector, the deposited fibers are subjected to circumferential stretching and directional alignment, which can obtain precursor nanofiber membranes with uniform fiber diameter and high orientation, laying the structural foundation for obtaining high-quality GDC solid electrolyte bulk material.
[0033] (II) Beneficial effects of GDC solid electrolyte blocks (1) The GDC solid electrolyte block provided by this invention has a microstructure in which nanofibers are stacked and arranged in a specific orientation and grains are oriented along the fiber axis. This microstructure not only improves the dimensional stability and structural uniformity of the block, but also provides a number of restricted three-dimensional reactive sites for the electrode / GDC interface that far exceed the conventional ones, greatly reducing the interfacial oxygen charge transfer resistance, so that the electrode reaction can still proceed smoothly at the working temperature of 400℃; on the other hand, it constructs an orientation path that is more conducive to the rapid transport of oxygen ions in the GDC electrolyte bulk phase, reducing the total resistance of grain boundaries to ion transport. The two effects work together to greatly reduce the interfacial resistance between the GDC solid electrolyte and the electrode at a low temperature of 400℃. For the first time, the potential oxygen sensor constructed based on this GDC solid electrolyte block can still accurately obtain a stable oxygen sensing response that conforms to the Nernst equation at 400℃, extending the lower limit temperature of the potential oxygen sensor during normal operation by at least 100℃, and there is still potential for further reduction. It is more suitable for fields such as automobile exhaust, industrial boilers and environmental gas monitoring.
[0034] (III) Beneficial effects of low-temperature operating GDC-based oxygen sensors (1) The oxygen sensor of the present invention employs a GDC solid electrolyte bulk material prepared by a specific process combining electrospinning and fiber-oriented cross-lamination and pressing. The internal structure of the GDC solid electrolyte bulk material has a microstructure in which nanofibers are stacked and arranged in a specific orientation and grains are oriented along the fiber axis. This microstructure not only improves the dimensional stability and structural uniformity of the GDC solid electrolyte bulk material, but also provides a far greater number of restricted three-dimensional reactive sites for the electrode / GDC interface than conventional ones, greatly reducing the interfacial oxygen charge transfer resistance, so that the electrode reaction can still proceed smoothly at a low temperature of 400℃. On the other hand, it constructs an orientation path that is more conducive to the rapid transport of oxygen ions in the GDC electrolyte bulk phase, reducing the total resistance of grain boundaries to ion transport. The two effects work together to greatly reduce the interfacial resistance between the GDC solid electrolyte and the electrode at a low temperature of 400℃, so that the low-temperature working GDC-based oxygen sensor of the present invention, constructed based on the GDC solid electrolyte bulk material, can not only accurately obtain a stable oxygen sensing response that conforms to the Nernst equation at a working temperature of 400℃, but also has accurate and reliable measurement, fast response speed, and good repeatability.
[0035] Compared to traditional potentiometric oxygen sensors that require operating temperatures above 500°C to function stably, the oxygen sensor of this invention extends the lower limit of normal operating temperature of potentiometric oxygen sensors by at least 100°C, and still has the potential to be further reduced. This expands its application possibilities in low-temperature environments and makes it more suitable for fields such as automotive exhaust, industrial boilers, and environmental gas monitoring.
[0036] (2) The oxygen sensor of the present invention uses GDC solid electrolyte bulk material prepared by electrospinning and lamination pressing process, which does not require expensive deposition equipment, making the overall manufacturing cost of the sensor relatively low. Moreover, the preparation process of each component of the sensor is compatible and easy to connect with existing ceramic sensor production lines, which has high industrial promotion value.
[0037] (3) The oxygen sensor of the present invention is designed with a sealed reference cavity on the reference electrode side, which is composed of a GDC solid electrolyte block, an LSM internal reference block, and a glass sealing layer. The sealed reference cavity is filled with a second porous platinum electrode. The gaseous oxygen in the cavity exists only in the electrode pores, and the total amount of gaseous oxygen is much smaller than the total amount of lattice oxygen that can be reversibly absorbed / released by the LSM internal reference block. At the operating temperature, the LSM internal reference block acts as a non-stoichiometric oxygen buffer material. The LSM internal reference block releases oxygen through its own Mn 3+ / Mn 4+The variable valence reversible absorption or release of trace amounts of oxygen stabilizes the oxygen partial pressure within the cavity at a constant level, providing a reference atmosphere with a constant oxygen partial pressure for the second porous platinum electrode. This provides a long-term stable and accurate reference potential for the oxygen sensor, eliminating the need for traditional electrochemical oxygen pump circuits and additional control circuits. This significantly simplifies the sensor structure, making the overall structure of the oxygen sensor simpler and more compact, reducing manufacturing costs, and improving long-term reliability. It is more suitable for fields such as automotive exhaust, industrial boilers, and environmental gas monitoring, and is more conducive to the application and promotion of oxygen sensors. Attached Figure Description
[0038] Figure 1 This is a schematic diagram of the structure of the low-temperature operating GDC-based oxygen sensor described in this invention.
[0039] Figure 2 The open-circuit potential response curve of the low-temperature operating GDC-based oxygen sensor in Embodiment 1 of the present invention is shown under the condition of alternating introduction of synthetic air and industrial nitrogen on the working electrode side.
[0040] Figure 3 The open-circuit potential response curve of the low-temperature operating GDC-based oxygen sensor in Embodiment 2 of the present invention under the condition of alternating introduction of synthetic air and industrial nitrogen on the working electrode side.
[0041] Figure 4 The open-circuit potential response curve of the low-temperature operating GDC-based oxygen sensor in Embodiment 3 of the present invention under the condition of alternating introduction of synthetic air and industrial nitrogen on the working electrode side.
[0042] Figure 5 The open-circuit potential response curves of the control group oxygen sensor under the same test conditions, with synthetic air and industrial nitrogen alternately introduced to the working electrode side. Detailed Implementation
[0043] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. Example 1
[0044] The present invention discloses a method for preparing a GDC solid electrolyte bulk material with an oriented nanofiber stacking structure, comprising the following steps:
[0045] (1) Weigh 0.834 g of hydrated cerium oxide and 0.220 g of hydrated gadolinium oxide according to a Gd doping molar fraction of 20%, and dissolve the weighed hydrated cerium oxide and hydrated gadolinium oxide together in 14 g of N,N-dimethylformamide (DMF) organic solvent.
[0046] Under magnetic stirring, add 1.04g of citric acid as a complexing agent and continue stirring until completely dissolved.
[0047] Subsequently, 1.4 g of polyvinylpyrrolidone (PVP) as a spinning carrier was added under stirring. The weight-average molecular weight of the PVP was 1.3 M. The mixture was stirred for 3 h to obtain a clear and transparent homogeneous spinning solution.
[0048] (2) Using electrospinning, the homogeneous spinning solution is electrospun onto the roller of the roller collector to obtain a precursor nanofiber membrane. Specifically, the homogeneous spinning solution obtained in step (1) is transferred to the electrospinning device and collected using a roller collector. Before electrospinning, a release substrate, such as silicone paper, is pre-laid on the surface of the roller of the roller collector. During the electrospinning process, the applied DC voltage is 16kV; the distance between the needle and the collector is 15cm; the spinning solution supply rate is 1.0mL / h; the roller of the roller collector rotates at a speed of 3000rpm; the roller collector is used to apply circumferential stretching and directional alignment to the deposited fibers. After spinning is completed, a precursor nanofiber membrane is obtained.
[0049] By regulating the rheological properties of the spinning solution through a two-component system of citric acid as a complexing agent and polyvinylpyrrolidone (PVP) as a spinning carrier, and by applying circumferential stretching and directional alignment to the deposited fibers through the high-speed rotation of the roller collector, a precursor nanofiber membrane with uniform fiber diameter and high orientation can be obtained, laying the structural foundation for obtaining high-quality GDC solid electrolyte bulk material in the future.
[0050] (3) Remove the precursor nanofiber membrane obtained in step (2) from the release substrate and lay it flat on a heat-resistant tray. To prevent the precursor nanofiber membrane from macroscopically curling during heat treatment, place several breathable weight sheets, such as alumina sheets, on the plane of the precursor nanofiber membrane at a spacing of 4 cm.
[0051] Subsequently, the heat-resistant tray is placed in an oven or furnace and treated at 240°C for 6 hours in an air atmosphere to pre-sinter the pre-driven nanofiber membrane, so that the fiber membrane completes the initial degreasing and pre-oxidative shrinkage to obtain a flat fiber sheet.
[0052] Next, the weighted sheet was removed, and the pre-sintered fiber sheet was transferred to a flat sintering plate. A breathable sheet was then pressed onto the surface of the fiber sheet to provide a small planar constraint to prevent warping during heat treatment. The temperature was then increased to 600°C at a rate of 8°C / min and held for 60 minutes to completely decompose the residual organic matter and form the GDC fluorite phase. After cooling, brittle GDC nanofiber sheets were obtained.
[0053] (4) Weigh the predetermined mass of the above-mentioned GDC nanofiber sheet, cut it into several small pieces, and stack these small pieces in a cylindrical pressing mold with an inner diameter of 6 mm in a cross-fiber orientation. Apply an axial pressure of 2 MPa to the stacked sheet at room temperature to densify and embed the stacked sheet to obtain a blank.
[0054] Next, the demolded blank is heated from room temperature to 600℃ at a heating rate of 8℃ / min and held for 30min for secondary sintering strengthening, finally obtaining a GDC solid electrolyte block with an oriented nanofiber stacking structure with a thickness of 1-3mm and a diameter of about 6mm.
[0055] The obtained GDC solid electrolyte bulk is composed of oriented nanofibers stacked inside, with a single fiber diameter of about 100-300 nm. A continuous interface network is formed between the fibers, and the grains exhibit directional growth characteristics along the fiber axis.
[0056] The GDC solid electrolyte bulk material with an oriented nanofiber stacking structure obtained by the above preparation method can be used to construct a potential-type oxygen sensor. For example... Figure 1 As shown, the structure of the low-temperature operating GDC-based oxygen sensor constructed based on the above-mentioned GDC solid electrolyte bulk with oriented nanofiber stacking structure includes: A GDC solid electrolyte block 1 having an oriented nanofiber stacking structure, the GDC solid electrolyte block 1 having opposing upper and lower surfaces; The first porous platinum electrode 2 is disposed on the lower surface of the GDC solid electrolyte block 1 as a working electrode; The first lead wire 7 is attached to the lower surface of the first porous platinum electrode 2 via conductive silver paste 9, and is used to lead out the potential signal of the first porous platinum electrode 2 as the working electrode. The second porous platinum electrode 3 is disposed on the upper surface of the GDC solid electrolyte block 1 as a reference electrode; LSM internal reference block 4 is disposed on the upper surface of the second porous platinum electrode 3; A platinum current collector layer 5 is disposed on the upper surface of the LSM internal reference block 4. The platinum current collector layer 5 is used to form a stable, low-resistance electrical contact with the LSM internal reference block 4, and to lead out the potential signal of the reference side through the second lead wire 8. The second lead wire 8 is attached to the upper surface of the platinum current collector layer 5 via conductive silver paste 9, and is used to lead out the potential signal of the second porous platinum electrode 8, which serves as a reference electrode, through the platinum current collector layer 5 and the LSM internal reference block 4. The glass sealing layer 6 covers all sides of the GDC solid electrolyte block 1, all seams between the side of the GDC solid electrolyte block 1 and the side of the second porous platinum electrode 3, all sides of the second porous platinum electrode 3, all seams between the side of the second porous platinum electrode 3 and the side of the LSM internal reference block 4, and all sides of the LSM internal reference block 4. The sealed reference cavity is formed by the GDC solid electrolyte block 1, the LSM internal reference block 4, and the glass sealing layer 6, and the second porous platinum electrode 3 is located inside the sealed reference cavity. The LSM internal reference block is prepared by weighing a predetermined amount of LSM powder and placing it in a tableting mold, pressing it into shape under a pressure of 2 MPa, sintering the shaped body at 1400℃ for 10 h to complete solid-state sintering and obtain a dense LSM internal reference block.
[0057] The first porous platinum electrode 2 is formed by sintering and solidifying a porous platinum electrode slurry coated on the lower surface of the GDC solid electrolyte block 1 at 880°C for 20 minutes. The second porous platinum electrode 3 is formed by sintering and solidifying a porous platinum electrode slurry that is bonded together with the upper surface of the GDC solid electrolyte block and the lower surface of the LSM internal reference block at 880°C for 20 minutes. The platinum current collector layer 5 is formed by sintering and solidifying a porous platinum electrode paste coated on the upper surface of the LSM internal reference block 4 at 880°C for 20 minutes. The glass sealing layer 6 is formed by coating a glass slurry made of low-melting-point glass powder and organic solvent, melting it at 880°C, and then cooling and solidifying it.
[0058] The fabrication steps of the above-mentioned low-temperature operating GDC-based oxygen sensor are as follows: S1: Take the GDC solid electrolyte block 1 with the above-mentioned oriented nanofiber stacked structure, and then coat a layer of platinum paste on the upper surface of the GDC solid electrolyte block 1 by screen printing or coating. Then place the pre-sintered LSM internal reference block 4 on the platinum paste. The GDC solid electrolyte block 1 and the LSM internal reference block 4 are bonded together as a whole by platinum paste. Then dry at 80-120°C. The platinum paste layer is the initial layer of the second porous platinum electrode 3. S2: Mix low-melting-point glass powder with an appropriate amount of organic solvent (such as ethanol) to prepare a viscous glass slurry. Apply the slurry to cover all sides of the GDC solid electrolyte block 1, all seams between the sides of the GDC solid electrolyte block 1 and the second porous platinum electrode 3, all sides of the second porous platinum electrode 3, all seams between the sides of the second porous platinum electrode 3 and the LSM internal reference block 4, and all sides of the LSM internal reference block 4. Then, heat the entire assembly coated with the glass slurry to 880°C at a heating rate of 2°C / min and hold for 20 minutes to allow the glass powder to melt and flow and form an airtight glass sealing layer. Then, cool and solidify to form a sealed reference cavity isolated from the outside. At the same time, the initial layer of the second porous platinum electrode 3, which is placed between the GDC solid electrolyte block 1 and the LSM internal reference block 4, is sintered and solidified in situ at 880°C to form the second porous platinum electrode 3. S3: Porous platinum electrode slurry is coated on the upper surface of the LSM internal reference block 4 and the lower surface of the GDC solid electrolyte block 1 of the above assembly. The temperature is raised to 880°C at a heating rate of 2°C / min and held for 20min. After curing, the porous platinum electrode slurry on the upper surface of the LSM internal reference block 4 forms a platinum current collector layer 5, and the porous platinum electrode slurry on the lower surface of the GDC solid electrolyte block 1 forms a first porous platinum electrode 2. S4: Finally, cut two lead wires, namely the first lead wire 7 and the second lead wire 8. Dip the first lead wire 7 in a small amount of conductive silver paste 9 and attach it to the first porous platinum electrode 2. Dip the second lead wire 8 in a small amount of conductive silver paste and attach it to the platinum current collector layer 5. Then cure at 180°C for 30 minutes to complete the potential signal extraction of the first porous platinum electrode 2 and the second porous platinum electrode 3. Example 2
[0059] The present invention discloses a method for preparing a GDC solid electrolyte bulk material with an oriented nanofiber stacking structure, comprising the following steps:
[0060] (1) Weigh 0.834 g of hydrated cerium oxide and 0.220 g of hydrated gadolinium oxide according to a Gd doping molar fraction of 20%, and dissolve the weighed hydrated cerium oxide and hydrated gadolinium oxide together in 14 g of N,N-dimethylformamide (DMF) organic solvent.
[0061] Under magnetic stirring, add 0.7g of citric acid as a complexing agent and continue stirring until completely dissolved.
[0062] Subsequently, 1.4 g of polyvinylpyrrolidone (PVP) as a spinning carrier was added under stirring. The weight-average molecular weight of the PVP was 1.3 M. The mixture was stirred for 3 h to obtain a clear and transparent homogeneous spinning solution.
[0063] (2) The homogeneous spinning solution is electrospun onto the roller of the roller collector to obtain a precursor nanofiber membrane. Specifically, the homogeneous spinning solution obtained in step (1) is transferred to the electrospinning device and collected by the roller collector. Before electrospinning, a release substrate, such as silicone paper, is pre-laid on the surface of the roller of the roller collector. During the electrospinning process, the applied DC voltage is 18kV; the distance between the needle and the collector is 13cm; the spinning solution supply rate is 2.0mL / h; the roller of the roller collector rotates at a speed of 3000rpm; the roller collector is used to apply circumferential stretching and directional alignment to the deposited fibers. After spinning is completed, a precursor nanofiber membrane is obtained.
[0064] By regulating the rheological properties of the spinning solution through a two-component system of citric acid as a complexing agent and polyvinylpyrrolidone (PVP) as a spinning carrier, and by applying circumferential stretching and directional alignment to the deposited fibers through the high-speed rotation of the roller collector, a precursor nanofiber membrane with uniform fiber diameter and high orientation can be obtained, laying the structural foundation for obtaining high-quality GDC solid electrolyte bulk material in the future.
[0065] (3) Remove the precursor nanofiber membrane obtained in step (2) from the release substrate and lay it flat on a heat-resistant tray. To prevent the precursor nanofiber membrane from macroscopically curling during heat treatment, place several breathable weight sheets, such as alumina sheets, on the plane of the precursor nanofiber membrane at a spacing of 4 cm.
[0066] Subsequently, the heat-resistant tray is placed in an oven or furnace and treated at 240°C for 8 hours in an air atmosphere to pre-sinter the pre-driven nanofiber membrane, so that the fiber membrane completes the initial degreasing and pre-oxidative shrinkage to obtain a flat fiber sheet.
[0067] Next, the weighted sheet was removed, and the pre-sintered fiber sheet was transferred to a flat sintering plate. A breathable sheet was then pressed onto the surface of the fiber sheet to provide a small planar constraint to prevent warping during heat treatment. The temperature was then increased to 600°C at a rate of 5°C / min and held for 120 minutes to completely decompose the residual organic matter and form the GDC fluorite phase. After cooling, brittle GDC nanofiber sheets were obtained.
[0068] (4) Weigh the GDC nanofiber sheet of the predetermined mass, cut it into several small pieces, and stack these small pieces in a cylindrical pressing mold with an inner diameter of 6 mm in a cross-fiber orientation. Apply an axial pressure of 1 MPa to the stacked sheet at room temperature to densify and embed the stacked sheet to obtain a blank.
[0069] Next, the demolded blank is heated from room temperature to 600℃ at a heating rate of 5℃ / min and held for 60min for secondary sintering strengthening, finally obtaining a GDC solid electrolyte block with an oriented nanofiber stacking structure with a thickness of 1-3mm and a diameter of about 6mm.
[0070] The obtained GDC solid electrolyte bulk is composed of oriented nanofibers stacked inside, with a single fiber diameter of about 100-300 nm. A continuous interface network is formed between the fibers, and the grains exhibit directional growth characteristics along the fiber axis.
[0071] The GDC solid electrolyte bulk material with an oriented nanofiber stacking structure obtained by the above preparation method can be used to construct a potential-type oxygen sensor. For example... Figure 1 As shown, the structure of the low-temperature operating GDC-based oxygen sensor constructed based on the above-mentioned GDC solid electrolyte bulk with oriented nanofiber stacking structure includes: A GDC solid electrolyte block 1 having an oriented nanofiber stacking structure, the GDC solid electrolyte block 1 having opposing upper and lower surfaces; The first porous platinum electrode 2 is disposed on the lower surface of the GDC solid electrolyte block 1 as a working electrode; The first lead wire 7 is attached to the lower surface of the first porous platinum electrode 2 via conductive silver paste 9, and is used to lead out the potential signal of the first porous platinum electrode 2 as the working electrode. The second porous platinum electrode 3 is disposed on the upper surface of the GDC solid electrolyte block 1 as a reference electrode; LSM internal reference block 4 is disposed on the upper surface of the second porous platinum electrode 3; A platinum current collector layer 5 is disposed on the upper surface of the LSM internal reference block 4. The platinum current collector layer 5 is used to form a stable, low-resistance electrical contact with the LSM internal reference block 4, and to lead out the potential signal of the reference side through the second lead wire 8. The second lead wire 8 is attached to the upper surface of the platinum current collector layer 5 via conductive silver paste 9, and is used to lead out the potential signal of the second porous platinum electrode 8, which serves as a reference electrode, through the platinum current collector layer 5 and the LSM internal reference block 4. The glass sealing layer 6 covers all sides of the GDC solid electrolyte block 1, all seams between the side of the GDC solid electrolyte block 1 and the side of the second porous platinum electrode 3, all sides of the second porous platinum electrode 3, all seams between the side of the second porous platinum electrode 3 and the side of the LSM internal reference block 4, and all sides of the LSM internal reference block 4. The sealed reference cavity is formed by the GDC solid electrolyte block 1, the LSM internal reference block 4, and the glass sealing layer 6, and the second porous platinum electrode 3 is located inside the sealed reference cavity. The LSM internal reference block is prepared by weighing a predetermined amount of LSM powder and placing it in a tableting mold, pressing it into shape under a pressure of 5 MPa, sintering the shaped body at 1300℃ for 8 hours to complete solid-state sintering and obtain a dense LSM internal reference block.
[0072] The first porous platinum electrode 2 is formed by sintering and solidifying a porous platinum electrode slurry coated on the lower surface of the GDC solid electrolyte block 1 at 880°C for 20 minutes. The second porous platinum electrode 3 is formed by sintering and solidifying a porous platinum electrode slurry that is bonded together with the upper surface of the GDC solid electrolyte block and the lower surface of the LSM internal reference block at 880°C for 20 minutes. The platinum current collector layer 5 is formed by sintering and solidifying a porous platinum electrode paste coated on the upper surface of the LSM internal reference block 4 at 880°C for 20 minutes. The glass sealing layer 6 is formed by coating a glass slurry made of low-melting-point glass powder and organic solvent, melting it at 880°C, and then cooling and solidifying it.
[0073] The fabrication steps of the above-mentioned low-temperature operating GDC-based oxygen sensor are as follows: S1: Take the GDC solid electrolyte block 1 with the above-mentioned oriented nanofiber stacked structure, and then coat a layer of platinum paste on the upper surface of the GDC solid electrolyte block 1 by screen printing or coating. Then place the pre-sintered LSM internal reference block 4 on the platinum paste. The GDC solid electrolyte block 1 and the LSM internal reference block 4 are bonded together as a whole by platinum paste. Then dry at 80-120°C. The platinum paste layer is the initial layer of the second porous platinum electrode 3. S2: Mix low-melting-point glass powder with an appropriate amount of organic solvent (such as ethanol) to prepare a viscous glass slurry. Apply the slurry to cover all sides of the GDC solid electrolyte block 1, all seams between the sides of the GDC solid electrolyte block 1 and the second porous platinum electrode 3, all sides of the second porous platinum electrode 3, all seams between the sides of the second porous platinum electrode 3 and the LSM internal reference block 4, and all sides of the LSM internal reference block 4. Then, heat the entire assembly coated with the glass slurry to 880°C at a heating rate of 5°C / min and hold for 20 minutes to allow the glass powder to melt and flow and form an airtight glass sealing layer. Then, cool and solidify to form a sealed reference cavity isolated from the outside. At the same time, the initial layer of the second porous platinum electrode 3, which is placed between the GDC solid electrolyte block 1 and the LSM internal reference block 4, is sintered and solidified in situ at 880°C to form the second porous platinum electrode 3. S3: Porous platinum electrode slurry is coated on the upper surface of the LSM internal reference block 4 and the lower surface of the GDC solid electrolyte block 1 of the above assembly. The temperature is raised to 880°C at a heating rate of 5°C / min and held for 20 min. After curing, the porous platinum electrode slurry on the upper surface of the LSM internal reference block 4 forms a platinum current collector layer 5, and the porous platinum electrode slurry on the lower surface of the GDC solid electrolyte block 1 forms a first porous platinum electrode 2. S4: Finally, cut two lead wires, namely the first lead wire 7 and the second lead wire 8. Dip the first lead wire 7 in a small amount of conductive silver paste 9 and attach it to the first porous platinum electrode 2. Dip the second lead wire 8 in a small amount of conductive silver paste and attach it to the platinum current collector layer 5. Then cure at 220°C for 15 minutes to complete the potential signal extraction of the first porous platinum electrode 2 and the second porous platinum electrode 3. Example 3
[0074] The present invention discloses a method for preparing a GDC solid electrolyte bulk material with an oriented nanofiber stacking structure, comprising the following steps:
[0075] (1) Weigh 0.834 g of hydrated cerium oxide and 0.377 g of hydrated gadolinium oxide according to a Gd doping molar fraction of 30%, and dissolve the weighed hydrated cerium oxide and hydrated gadolinium oxide together in 14 g of N,N-dimethylformamide (DMF) organic solvent.
[0076] Under magnetic stirring, add 0.9g of citric acid as a complexing agent and continue stirring until completely dissolved.
[0077] Subsequently, 1.6 g of polyvinylpyrrolidone (PVP) as a spinning carrier was added under stirring. The weight-average molecular weight of the PVP was 1.3 M. The mixture was stirred for 3 h to obtain a clear and transparent homogeneous spinning solution.
[0078] (2) The homogeneous spinning solution is electrospun onto the roller of the roller collector to obtain a precursor nanofiber membrane. Specifically, the homogeneous spinning solution obtained in step (1) is transferred to the electrospinning device and collected by the roller collector. Before electrospinning, a release substrate, such as silicone paper, is pre-laid on the surface of the roller of the roller collector. During the electrospinning process, the applied DC voltage is 20kV; the distance between the needle and the collector is 17cm; the spinning solution supply rate is 0.8mL / h; the roller of the roller collector rotates at a speed of 3000rpm; the roller collector is used to apply circumferential stretching and directional alignment to the deposited fibers. After spinning is completed, a precursor nanofiber membrane is obtained.
[0079] By regulating the rheological properties of the spinning solution through a two-component system of citric acid as a complexing agent and polyvinylpyrrolidone (PVP) as a spinning carrier, and by applying circumferential stretching and directional alignment to the deposited fibers through the high-speed rotation of the roller collector, a precursor nanofiber membrane with uniform fiber diameter and high orientation can be obtained, laying the structural foundation for obtaining high-quality GDC solid electrolyte bulk material in the future.
[0080] (3) Remove the precursor nanofiber membrane obtained in step (2) from the release substrate and lay it flat on a heat-resistant tray. To prevent the precursor nanofiber membrane from macroscopically curling during heat treatment, place several breathable weight sheets, such as alumina sheets, on the plane of the precursor nanofiber membrane at a spacing of 4 cm.
[0081] Subsequently, the heat-resistant tray is placed in an oven or furnace and treated at 200°C for 4 hours in an air atmosphere to pre-sinter the pre-driven nanofiber membrane, so that the fiber membrane completes the initial degreasing and pre-oxidative shrinkage to obtain a flat fiber sheet.
[0082] Next, the weighted sheet was removed, and the pre-sintered fiber sheet was transferred to a flat sintering plate. A breathable sheet was then pressed onto the surface of the fiber sheet to provide micro-planar constraints, preventing warping during heat treatment. The temperature was then increased to 600°C at a rate of 10°C / min and held for 30 minutes to completely decompose the residual organic matter and form the GDC fluorite phase. After cooling, brittle GDC nanofiber sheets were obtained.
[0083] (4) Weigh the GDC nanofiber sheet of the predetermined mass, cut it into several small pieces, and stack these small pieces in a cylindrical pressing mold with an inner diameter of 6 mm in a cross-fiber orientation. Apply an axial pressure of 1 MPa to the stacked sheet at room temperature to densify and embed the stacked sheet to obtain a blank.
[0084] Next, the demolded blank is heated from room temperature to 600℃ at a heating rate of 10℃ / min and held for 20min for secondary sintering strengthening, finally obtaining a GDC solid electrolyte block with an oriented nanofiber stacking structure with a thickness of 1-3mm and a diameter of about 6mm.
[0085] The obtained GDC solid electrolyte bulk is composed of oriented nanofibers stacked inside, with a single fiber diameter of about 100-300 nm. A continuous interface network is formed between the fibers, and the grains exhibit directional growth characteristics along the fiber axis.
[0086] The GDC solid electrolyte bulk material with an oriented nanofiber stacking structure obtained by the above preparation method can be used to construct a potential-type oxygen sensor. For example... Figure 1As shown, the structure of the low-temperature operating GDC-based oxygen sensor constructed based on the above-mentioned GDC solid electrolyte bulk with oriented nanofiber stacking structure includes: A GDC solid electrolyte block 1 having an oriented nanofiber stacking structure, the GDC solid electrolyte block 1 having opposing upper and lower surfaces; The first porous platinum electrode 2 is disposed on the lower surface of the GDC solid electrolyte block 1 as a working electrode; The first lead wire 7 is attached to the lower surface of the first porous platinum electrode 2 via conductive silver paste 9, and is used to lead out the potential signal of the first porous platinum electrode 2 as the working electrode. The second porous platinum electrode 3 is disposed on the upper surface of the GDC solid electrolyte block 1 as a reference electrode; LSM internal reference block 4 is disposed on the upper surface of the second porous platinum electrode 3; A platinum current collector layer 5 is disposed on the upper surface of the LSM internal reference block 4. The platinum current collector layer 5 is used to form a stable, low-resistance electrical contact with the LSM internal reference block 4, and to lead out the potential signal of the reference side through the second lead wire 8. The second lead wire 8 is attached to the upper surface of the platinum current collector layer 5 via conductive silver paste 9, and is used to lead out the potential signal of the second porous platinum electrode 8, which serves as a reference electrode, through the platinum current collector layer 5 and the LSM internal reference block 4. The glass sealing layer 6 covers all sides of the GDC solid electrolyte block 1, all seams between the side of the GDC solid electrolyte block 1 and the side of the second porous platinum electrode 3, all sides of the second porous platinum electrode 3, all seams between the side of the second porous platinum electrode 3 and the side of the LSM internal reference block 4, and all sides of the LSM internal reference block 4. The sealed reference cavity is formed by the GDC solid electrolyte block 1, the LSM internal reference block 4, and the glass sealing layer 6, and the second porous platinum electrode 3 is located inside the sealed reference cavity. The LSM internal reference block is prepared by weighing a predetermined amount of LSM powder and placing it in a tableting mold, pressing it into shape under a pressure of 5 MPa, sintering the shaped body at 1300℃ for 8 hours to complete solid-state sintering and obtain a dense LSM internal reference block.
[0087] The first porous platinum electrode 2 is formed by sintering and solidifying a porous platinum electrode slurry coated on the lower surface of the GDC solid electrolyte block 1 at 880°C for 30 minutes. The second porous platinum electrode 3 is formed by sintering and solidifying a porous platinum electrode slurry that is bonded together with the upper surface of the GDC solid electrolyte block and the lower surface of the LSM internal reference block at 880°C for 30 minutes. The platinum current collector layer 5 is formed by sintering and solidifying a porous platinum electrode paste coated on the upper surface of the LSM internal reference block 4 at 880°C for 30 minutes. The glass sealing layer 6 is formed by coating a glass slurry made of low-melting-point glass powder and organic solvent, melting it at 880°C, and then cooling and solidifying it.
[0088] The fabrication steps of the above-mentioned low-temperature operating GDC-based oxygen sensor are as follows: S1: Take the GDC solid electrolyte block 1 with the above-mentioned oriented nanofiber stacked structure, and then coat a layer of platinum paste on the upper surface of the GDC solid electrolyte block 1 by screen printing or coating. Then place the pre-sintered LSM internal reference block 4 on the platinum paste. The GDC solid electrolyte block 1 and the LSM internal reference block 4 are bonded together as a whole by platinum paste. Then dry at 80-120°C. The platinum paste layer is the initial layer of the second porous platinum electrode 3. S2: Mix low-melting-point glass powder with an appropriate amount of organic solvent (such as ethanol) to prepare a viscous glass slurry. Apply the slurry to cover all sides of the GDC solid electrolyte block 1, all seams between the sides of the GDC solid electrolyte block 1 and the second porous platinum electrode 3, all sides of the second porous platinum electrode 3, all seams between the sides of the second porous platinum electrode 3 and the LSM internal reference block 4, and all sides of the LSM internal reference block 4. Then, heat the entire assembly coated with the glass slurry to 880°C at a heating rate of 5°C / min and hold for 30 minutes to allow the glass powder to melt and flow and form an airtight glass sealing layer. Then, cool and solidify to form a sealed reference cavity isolated from the outside. At the same time, the initial layer of the second porous platinum electrode 3, which is placed between the GDC solid electrolyte block 1 and the LSM internal reference block 4, is sintered and solidified in situ at 880°C to form the second porous platinum electrode 3. S3: A porous platinum electrode slurry is coated on the upper surface of the LSM internal reference block 4 and the lower surface of the GDC solid electrolyte block 1 of the above assembly. The temperature is raised to 880°C at a heating rate of 5°C / min and held for 30 min. After curing, the porous platinum electrode slurry on the upper surface of the LSM internal reference block 4 forms a platinum current collector layer 5, and the porous platinum electrode slurry on the lower surface of the GDC solid electrolyte block 1 forms a first porous platinum electrode 2. S4: Finally, cut two lead wires, namely the first lead wire 7 and the second lead wire 8. Dip the first lead wire 7 in a small amount of conductive silver paste 9 and attach it to the first porous platinum electrode 2. Dip the second lead wire 8 in a small amount of conductive silver paste and attach it to the platinum current collector layer 5. Then cure at 220°C for 15 minutes to complete the potential signal extraction of the first porous platinum electrode 2 and the second porous platinum electrode 3.
[0089] It should be noted that the LSM material used for preparing the LSM internal reference bulk in the oxygen sensor of the present invention is a known commercially available material. The LSM, namely Lanthanum Strontium Manganite, the full English name of which is Lanthanum Strontium Manganite (abbreviated as LSM), is a perovskite-type ABO3 composite oxide, with the general chemical formula La 1-x Sr x MnO3(0<x<1). LSM has a fixed thermodynamic equilibrium oxygen partial pressure at a given temperature. At the working temperature, the LSM internal reference bulk itself acts as an oxygen chemical buffer. The LSM internal reference bulk reversibly absorbs or releases a trace amount of oxygen through the variable valence state of Mn 3+ / Mn 4+ , so as to dynamically and stably maintain the oxygen partial pressure in the sealed reference chamber at a constant value determined by the intrinsic characteristics of the LSM material, thereby providing a stable reference potential for the sensor.
[0090] It should also be noted that the stabilizing effect of the LSM internal reference bulk on the oxygen partial pressure in the sealed reference chamber has a buffer capacity limit. In the present invention, the inner space of the sealed reference chamber is filled with the second porous platinum electrode, and the gas-phase oxygen in the chamber only exists in the pores of the second porous platinum electrode, so that the total amount of gas-phase oxygen in the chamber is far less than the total amount of lattice oxygen that can be reversibly absorbed or released by the LSM internal reference bulk at the working temperature, thereby ensuring that the LSM internal reference bulk can completely lock and maintain the oxygen partial pressure in the chamber at a constant value, and realize a long-term stable reference potential.
[0091] The working principle of the low-temperature working GDC-based oxygen sensor of the present invention is as follows: When the sensor is placed at a working temperature of 400°C, the GDC solid electrolyte bulk 1 exhibits good oxygen ion conductivity; the LSM internal reference bulk 4 reversibly absorbs or releases a trace amount of oxygen through the valence change of Mn at high temperature 3+ / Mn 4+ , so as to stabilize the oxygen partial pressure in the sealed reference chamber at a constant value determined by the intrinsic characteristics of the LSM material, that is, the reference oxygen partial pressure is constant; the first porous platinum electrode 2 serves as the working electrode to contact the gas to be measured; since the oxygen partial pressure of the gas to be measured is different from the reference oxygen partial pressure in the sealed reference chamber, an oxygen concentration difference is formed on both sides of the sensor; at high temperature, the porous platinum electrode has catalytic activity, which promotes the conversion between oxygen molecules and oxygen ions.
[0092] When the oxygen partial pressure on the side of the first porous platinum electrode 2 is higher than the reference oxygen partial pressure, the oxygen molecules on the side of the first porous platinum electrode 2 absorb electrons from the first porous platinum electrode 2 to become oxygen ions, and a reduction reaction occurs on this side: O2+4e⁻→2O²⁻; the platinum electrode on this side consumes electrons, and the potential rises; Oxygen ions migrate from the interior of the GDC solid electrolyte block 1 to the reference side of the second porous platinum electrode 3. After releasing electrons, the oxygen ions become oxygen molecules and diffuse into the sealed reference cavity (the pores of the second porous platinum electrode). An oxidation reaction occurs on the second porous platinum electrode 3 side: 2O²⁻→O₂+4e⁻. Electrons are released on this side, the potential decreases, and as the number of oxygen molecules increases, the oxygen partial pressure in the sealed reference cavity continuously increases. When the oxygen partial pressure in the sealed reference cavity exceeds the equilibrium value, the lattice in the LSM internal reference block 4 absorbs free oxygen, and the Mn in the LSM internal reference block 4... 3+ Oxidized to Mn 4+ This brings the reference oxygen partial pressure back to the equilibrium value.
[0093] When the oxygen partial pressure on the first porous platinum electrode 2 side is lower than the reference oxygen partial pressure, a reduction reaction occurs on the second porous platinum electrode 3 side (the side with high oxygen partial pressure) within the sealed reference cavity: oxygen molecules in the sealed reference cavity (the pores of the second porous platinum electrode) absorb electrons from the second porous platinum electrode 3 to become oxygen ions, and a reduction reaction occurs on this side: O2 + 4e⁻ → 2O²⁻. The platinum electrode on this side consumes electrons, and the potential increases. During the above process, because the second porous platinum electrode 3 side continuously consumes oxygen molecules in the sealed reference cavity, the oxygen partial pressure in the sealed reference cavity tends to decrease. When the oxygen partial pressure in the cavity is lower than the equilibrium value of the LSM internal reference block 4, the lattice in the LSM internal reference block 4 releases trace amounts of oxygen, and the Mn in the LSM internal reference block 4... 4+ Reduced to Mn 3+ The trace amount of oxygen released from the lattice replenishes the sealed reference cavity, thereby pulling the reference oxygen partial pressure back to the equilibrium value.
[0094] Oxygen ions migrate from the interior of the GDC solid electrolyte block 1 to the side of the first porous platinum electrode 2. After releasing electrons, the oxygen ions become oxygen molecules and diffuse into the gas to be measured. An oxidation reaction occurs on the side of the first porous platinum electrode 2 (the side with low oxygen partial pressure): 2O²⁻→O2+4e⁻. Due to the release of electrons, the potential on this side decreases.
[0095] Through the reversible oxygen absorption and release process described above, the LSM internal reference block 4 always keeps the oxygen partial pressure in the sealed reference cavity at a constant level determined by the intrinsic properties of the material, thereby providing a stable reference potential for the sensor.
[0096] The aforementioned electrode reactions and oxygen ion migration processes result in a difference in the electron chemical potentials on both sides of the first porous platinum electrode 2 and the second porous platinum electrode 3. This difference in electron chemical potentials forms an open-circuit potential difference E, and the relationship between this open-circuit potential difference E and the oxygen partial pressures on both sides follows the Nernst equation: E = (RT / 4F)ln(pO2 + / pO2 - ); pO2+ The reference oxygen partial pressure (a known constant determined by LSM internal reference block 4) is the stable reference oxygen partial pressure of LSM internal reference block 4, pO2. - The oxygen partial pressure of the gas to be measured is given by the first porous platinum electrode 2, where R is the gas constant, T is the absolute temperature, and F is the Faraday constant. The oxygen partial pressure of the gas to be measured can be calculated by measuring the open-circuit potential difference E between the first lead wire 7 and the second lead wire 8, thus achieving oxygen concentration detection. The glass sealing layer 6 ensures that the sealed reference cavity is isolated from the external gas, preventing interference from the external atmosphere on the LSM internal reference block 4, thereby providing a long-term stable reference potential and ensuring the accuracy and reliability of the sensor measurement.
[0097] Sensor performance testing: (1) The low-temperature working GDC-based oxygen sensors prepared in Examples 1, 2, and 3 of this invention, and a control oxygen sensor of the same size and electrode structure constructed based on a GDC solid electrolyte block made by a conventional solid-state method (hereinafter referred to as the control group) were placed in the test system respectively (i.e., the oxygen sensor of this invention and the control oxygen sensor were compared in terms of performance, the only difference between the two was the GDC solid electrolyte block. The oxygen sensor of this invention used a GDC solid electrolyte block with an oriented nanofiber stacking structure, while the control oxygen sensor used a GDC solid electrolyte block without an oriented nanofiber stacking structure made by a conventional solid-state method). At a working temperature of 400°C, synthetic air with an oxygen volume fraction of 21% and industrial nitrogen with a residual oxygen volume fraction of 0.01% to 0.1% were alternately introduced into the working electrode side of each low-temperature working GDC-based oxygen sensor and the control oxygen sensor for calibration, and then the output signal was measured. Under the same test conditions and monitored using a CHI604D electrochemical workstation, the test results are shown in Table 1 below. Table 1 shows the output signal amplitude and signal-to-noise ratio of the low-temperature GDC-based oxygen sensor in each embodiment and the oxygen sensor in the control group.
[0098]
[0099] As shown in Table 1 above, the signal-to-noise ratio (SNR) of each sensor in each embodiment of the present invention is significantly higher than that of the control group. Specifically, compared with the control group, the SNR of Embodiment 1 is improved by approximately 35 times, the SNR of Embodiment 2 by approximately 26 times, and the SNR of Embodiment 3 by approximately 30 times, indicating that the oxygen sensor of the present invention has excellent signal quality. The high SNR ensures that the output signal of the sensor can be clearly and stably distinguished, providing a reliable signal basis for subsequent accurate calculation of oxygen concentration based on the Nernst equation. This is a prerequisite for achieving high-precision measurement and helps to ensure the measurement accuracy of the oxygen sensor.
[0100] The formula for calculating the signal-to-noise ratio (SNR) is as follows: SNR = S / N; Where S is the amplitude of the sensor output signal and N is the instrument's noise floor.
[0101] In this performance test, the open-circuit potential response curves of the low-temperature GDC-based oxygen sensors of Examples 1, 2, and 3 were monitored using a CHI604D electrochemical workstation under the above-mentioned alternating introduction of syngas and industrial nitrogen. The results are as follows: The open-circuit potential response curve of the cryogenic GDC-based oxygen sensor in Example 1 under the above-mentioned alternating introduction of synthetic air and industrial nitrogen is shown below. Figure 2 As shown, Figure 2 The horizontal axis represents the test time (in seconds), and the vertical axis represents the open-circuit potential (in volts).
[0102] Depend on Figure 2 It can be seen that after the atmosphere switch, the open-circuit potential of the oxygen sensor in Embodiment 1 of the present invention can quickly reach a steady state and form a significant potential plateau: when synthetic air is introduced, the potential is maintained at a relatively high potential plateau (approximately -0.09 V); when industrial nitrogen is introduced, the potential is maintained at a relatively low potential plateau (approximately -0.29 V). The steady-state open-circuit potential difference ΔE under the two atmospheres is approximately 198 mV, indicating that the oxygen sensor of the present invention can produce a significant response signal to changes in oxygen concentration at 400℃, demonstrating that the sensor is sensitive to changes in oxygen concentration; compared to the control group oxygen sensor which has almost no response at the same temperature, this is a qualitative breakthrough. Furthermore, Figure 2 The potential values of each steady-state platform are generally stable with small fluctuations, and there is no obvious drift in the potential of the platform segment, indicating that the sensor has high single-detection accuracy. The curves of the two rounds of atmosphere cycle tests are highly overlapping, indicating that the sensor has good consistency in repeated measurements, stable and reliable output data, and excellent working repeatability and stability, which can accurately and stably reflect atmospheres with different oxygen contents.
[0103] The open-circuit potential response curve of the cryogenic GDC-based oxygen sensor in Example 2 under the above-mentioned alternating introduction of synthetic air and industrial nitrogen is shown in the figure below. Figure 3 As shown, Figure 3 The horizontal axis represents the test time (in seconds), and the vertical axis represents the open-circuit potential (in volts).
[0104] Depend on Figure 3It can be seen that after the atmosphere switch, the open-circuit potential of the oxygen sensor in Embodiment 1 of the present invention can quickly reach a steady state and form a significant potential plateau: when synthetic air is introduced, the potential is maintained at a relatively high potential plateau (approximately -0.07 V); when industrial nitrogen is introduced, the potential is maintained at a relatively low potential plateau (approximately -0.077 V). The steady-state open-circuit potential difference ΔE under the two atmospheres is approximately 147 mV, indicating that the oxygen sensor of the present invention can produce a significant response signal to changes in oxygen concentration at 400°C, demonstrating that the sensor is highly sensitive to changes in oxygen concentration; compared to the control group oxygen sensor which has almost no response at the same temperature, this is a qualitative breakthrough. Furthermore, Figure 3 The potential values of each steady-state platform are generally stable with small fluctuations, and there is no obvious drift in the potential of the platform segment, indicating that the sensor has high single-detection accuracy. The curves of the two rounds of atmosphere cycle tests are highly overlapping, indicating that the sensor has good consistency in repeated measurements, stable and reliable output data, and excellent working repeatability and stability, which can accurately and stably reflect atmospheres with different oxygen contents.
[0105] The open-circuit potential response curve of the cryogenic GDC-based oxygen sensor in Example 3 under the above-mentioned alternating introduction of synthetic air and industrial nitrogen is shown in the figure below. Figure 4 As shown, Figure 4 The horizontal axis represents the test time (in seconds), and the vertical axis represents the open-circuit potential (in volts).
[0106] Depend on Figure 4 It can be seen that after the atmosphere switch, the open-circuit potential of the oxygen sensor in Embodiment 1 of the present invention can quickly reach a steady state and form a significant potential plateau: when synthetic air is introduced, the potential is maintained at a relatively high potential plateau (approximately -0.03V); when industrial nitrogen is introduced, the potential is maintained at a relatively low potential plateau (approximately -0.21V). The steady-state open-circuit potential difference ΔE under the two atmospheres is approximately 181mV, indicating that the oxygen sensor of the present invention can produce a significant response signal to changes in oxygen concentration at 400℃, demonstrating that the sensor is sensitive to changes in oxygen concentration; compared to the control group oxygen sensor which has almost no response at the same temperature, this is a qualitative breakthrough. Furthermore, Figure 4 The potential values of each steady-state platform are generally stable with small fluctuations, and there is no obvious drift in the potential of the platform segment, indicating that the sensor has high single-detection accuracy. The curves of the two rounds of atmosphere cycle tests are highly overlapping, indicating that the sensor has good consistency in repeated measurements, stable and reliable output data, and excellent working repeatability and stability, which can accurately and stably reflect atmospheres with different oxygen contents.
[0107] The open-circuit potential response curve of the control group oxygen sensor under the above-mentioned alternating introduction of synthetic air and industrial nitrogen is shown in the figure below. Figure 5 As shown, Figure 5 The horizontal axis represents the test time (in seconds), and the vertical axis represents the open-circuit potential (in volts).
[0108] Depend on Figure 5 It can be seen that although the open-circuit potential of the sensor changes after the atmosphere switch, the response process is slow and no obvious and stable potential plateau is formed. Moreover, when synthetic air and industrial nitrogen are introduced, the steady-state open-circuit potential difference ΔE under the two atmospheres is only about 15mV, which is far lower than the theoretical value calculated by the Nernst equation at this temperature. This indicates that the control group oxygen sensor has a weak response signal to changes in oxygen concentration, suggesting that the control group oxygen sensor is not sensitive to changes in oxygen concentration and cannot effectively distinguish atmospheres with different oxygen contents. At the same time, Figure 5 Even after the atmosphere stabilized, the curve did not form a clear and stable potential plateau. The potential fluctuated violently in the plateau segment, and the amplitude drift was obvious. This indicates that the voltage stability of the comparative oxygen sensor is poor, the single detection accuracy is low, and the measurement results are unreliable. It cannot stably reflect the changes in atmospheres with different oxygen contents, which verifies the limitations of the oxygen response performance of traditional GDC-based sensors at 400℃.
[0109] (2) The accuracy of the low-temperature working GDC-based oxygen sensor prepared in Example 1 of the present invention was further tested. The low-temperature working GDC-based oxygen sensor of Example 1 of the present invention was calibrated in the test system with air and a standard gas with a 1% oxygen concentration. After calibration, air and a standard gas with a 1% oxygen concentration were repeatedly introduced to test the voltage of the sensor in the 1% concentration standard gas, and the voltage was converted into the corresponding oxygen concentration according to the Nernst equation. The calibration and test temperatures were both 370°C. The test results are shown in Table 2 below.
[0110]
[0111] As shown in Table 2, the absolute measurement error of the low-temperature operating GDC-based oxygen sensor prepared in Example 1 of this invention is within 0.15% under a standard gas with a 1% oxygen concentration, meeting the accuracy requirements of commercially available oxygen sensors. This indicates that the low-temperature operating GDC-based oxygen sensor of this invention is accurate and highly reliable. When tested under the same conditions, the control group failed to produce consistent voltage output values for the same oxygen concentration. Example 1 of this invention demonstrates a significant technical advantage over the control group.
[0112] (3) The low-temperature working type GDC-based oxygen sensor prepared in Example 2 of the present invention was placed in the test system and calibrated in clean air. After calibration, industrial nitrogen and clean air were repeatedly introduced to test the voltage of the sensor in clean air and convert it into the corresponding oxygen concentration according to the Nernst equation. The calibration and test temperature was 390℃. The test results are shown in Table 3 below.
[0113]
[0114] As shown in Table 3, the absolute measurement error of the low-temperature operating GDC-based oxygen sensor prepared in Example 2 of this invention is within 0.53% under clean air, meeting the accuracy requirements of commercially available oxygen sensors. This indicates that the low-temperature operating GDC-based oxygen sensor of this invention is accurate and highly reliable. When tested under the same conditions, the control group failed to produce consistent voltage output values for the same oxygen concentration. Example 2 of this invention demonstrates a significant technical advantage over the control group.
[0115] In summary, based on the test results in Tables 2 and 3, the oxygen sensor of Example 1 of this invention exhibits an absolute measurement error of no more than 0.15% VOL for 1% O2 at 370℃, and the oxygen sensor of Example 2 exhibits an absolute measurement error of no more than 0.53% VOL for 21% O2 at 390℃, both exceeding the accuracy requirements of commercially available oxygen sensors. Furthermore, since the oxygen ion conductivity of the GDC solid electrolyte increases with increasing operating temperature, and the charge transfer reaction rate at the electrode interface also accelerates, the signal output stability and measurement accuracy of the sensor of this invention show an increasing trend as the operating temperature rises from 370℃ to 400℃. Therefore, since the sensor of this invention already possesses high accuracy at 370℃ and 390℃, its measurement accuracy at 400℃ is no lower than the aforementioned levels, and may even be superior. Thus, the sensor of this invention also exhibits excellent measurement accuracy and reliability at an operating temperature of 400℃.
[0116] The advantages of this invention are: (I) Beneficial effects of the GDC solid electrolyte bulk preparation method (1) The GDC solid electrolyte bulk prepared by this method has stable and reliable quality. By combining electrospinning with fiber orientation cross-lamination and sintering process, a microstructure is formed inside the GDC solid electrolyte bulk, in which nanofibers are stacked and arranged in a specific orientation and grains are oriented along the fiber axis. This microstructure not only improves the dimensional stability and structural uniformity of the bulk, but also provides a number of restricted three-dimensional reactive sites for the electrode / GDC interface that far exceed the conventional ones, greatly reducing the oxygen charge transfer resistance at the interface, so that the electrode reaction can still proceed smoothly at the working temperature of 400℃; on the other hand, it constructs an orientation path that is more conducive to the rapid transport of oxygen ions in the GDC electrolyte bulk phase, reducing the total resistance of grain boundaries to ion transport. The synergistic effect of the two effects significantly reduces the interfacial resistance between the GDC solid electrolyte and the electrode at a low temperature of 400℃. For the first time, a potential-type oxygen sensor constructed based on this GDC solid electrolyte block can still accurately obtain a stable oxygen sensing response that conforms to the Nernst equation at 400℃. This extends the lower limit temperature for normal operation of the potential-type oxygen sensor by at least 100℃, and there is still potential for further reduction. It is more suitable for fields such as automobile exhaust, industrial boilers and environmental gas monitoring.
[0117] (2) The preparation method is simple and the manufacturing cost is relatively low. It can be achieved by using electrospinning equipment and pressing equipment, without the need for complex and expensive deposition equipment. At the same time, the preparation method has good process compatibility and is easy to connect with existing ceramic sensor production lines, and has high industrial promotion value.
[0118] (3) This preparation method regulates the rheological properties of the spinning solution by using a two-component system of citric acid as a complexing agent and polyvinylpyrrolidone (PVP) as a spinning carrier. Combined with the high-speed rotation of the roller collector, the deposited fibers are subjected to circumferential stretching and directional alignment, which can obtain precursor nanofiber membranes with uniform fiber diameter and high orientation, laying the structural foundation for obtaining high-quality GDC solid electrolyte bulk material.
[0119] (II) Beneficial effects of GDC solid electrolyte blocks (1) The GDC solid electrolyte block provided by this invention has a microstructure in which nanofibers are stacked and arranged in a specific orientation and grains are oriented along the fiber axis. This microstructure not only improves the dimensional stability and structural uniformity of the block, but also provides a number of restricted three-dimensional reactive sites for the electrode / GDC interface that far exceed the conventional ones, greatly reducing the interfacial oxygen charge transfer resistance, so that the electrode reaction can still proceed smoothly at the working temperature of 400℃; on the other hand, it constructs an orientation path that is more conducive to the rapid transport of oxygen ions in the GDC electrolyte bulk phase, reducing the total resistance of grain boundaries to ion transport. The two effects work together to greatly reduce the interfacial resistance between the GDC solid electrolyte and the electrode at a low temperature of 400℃. For the first time, the potential oxygen sensor constructed based on this GDC solid electrolyte block can still accurately obtain a stable oxygen sensing response that conforms to the Nernst equation at 400℃, extending the lower limit temperature of the potential oxygen sensor during normal operation by at least 100℃, and there is still potential for further reduction. It is more suitable for fields such as automobile exhaust, industrial boilers and environmental gas monitoring.
[0120] (III) Beneficial effects of low-temperature operating GDC-based oxygen sensors (1) The oxygen sensor of the present invention employs a GDC solid electrolyte bulk material prepared by a specific process combining electrospinning and fiber-oriented cross-lamination and pressing. The internal structure of the GDC solid electrolyte bulk material has a microstructure in which nanofibers are stacked and arranged in a specific orientation and grains are oriented along the fiber axis. This microstructure not only improves the dimensional stability and structural uniformity of the GDC solid electrolyte bulk material, but also provides a far greater number of restricted three-dimensional reactive sites for the electrode / GDC interface than conventional ones, greatly reducing the interfacial oxygen charge transfer resistance, so that the electrode reaction can still proceed smoothly at a low temperature of 400℃. On the other hand, it constructs an orientation path that is more conducive to the rapid transport of oxygen ions in the GDC electrolyte bulk phase, reducing the total resistance of grain boundaries to ion transport. The two effects work together to greatly reduce the interfacial resistance between the GDC solid electrolyte and the electrode at a low temperature of 400℃, so that the low-temperature working GDC-based oxygen sensor of the present invention, constructed based on the GDC solid electrolyte bulk material, can not only accurately obtain a stable oxygen sensing response that conforms to the Nernst equation at a working temperature of 400℃, but also has accurate and reliable measurement, fast response speed, and good repeatability.
[0121] Compared to traditional potentiometric oxygen sensors that require operating temperatures above 500°C to function stably, the oxygen sensor of this invention extends the lower limit of normal operating temperature of potentiometric oxygen sensors by at least 100°C, and still has the potential to be further reduced. This expands its application possibilities in low-temperature environments and makes it more suitable for fields such as automotive exhaust, industrial boilers, and environmental gas monitoring.
[0122] (2) The oxygen sensor of the present invention uses GDC solid electrolyte bulk material prepared by electrospinning and lamination pressing process, which does not require expensive deposition equipment, making the overall manufacturing cost of the sensor relatively low. Moreover, the preparation process of each component of the sensor is compatible and easy to connect with existing ceramic sensor production lines, which has high industrial promotion value.
[0123] (3) The oxygen sensor of the present invention is designed with a sealed reference cavity on the reference electrode side, which is composed of a GDC solid electrolyte block, an LSM internal reference block, and a glass sealing layer. The sealed reference cavity is filled with a second porous platinum electrode. The gaseous oxygen in the cavity exists only in the electrode pores, and the total amount of gaseous oxygen is much smaller than the total amount of lattice oxygen that can be reversibly absorbed / released by the LSM internal reference block. At the operating temperature, the LSM internal reference block acts as a non-stoichiometric oxygen buffer material. The LSM internal reference block releases oxygen through its own Mn 3+ / Mn 4+ The variable valence reversible absorption or release of trace amounts of oxygen stabilizes the oxygen partial pressure within the cavity at a constant level, providing a reference atmosphere with a constant oxygen partial pressure for the second porous platinum electrode. This provides a long-term stable and accurate reference potential for the oxygen sensor, eliminating the need for traditional electrochemical oxygen pump circuits and additional control circuits. This significantly simplifies the sensor structure, making the overall structure of the oxygen sensor simpler and more compact, reducing manufacturing costs, and improving long-term reliability. It is more suitable for fields such as automotive exhaust, industrial boilers, and environmental gas monitoring, and is more conducive to the application and promotion of oxygen sensors.
[0124] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any other way. Any modifications or equivalent changes made based on the technical essence of the present invention shall still fall within the scope of protection claimed by the present invention.
Claims
1. A method for preparing a GDC solid electrolyte bulk material with an oriented nanofiber stacking structure, characterized in that: Includes the following steps: (1) Weigh out cerium source and gadolinium source according to Gd doping molar fraction of 20% to 30%, and dissolve them together in an organic solvent. Then add citric acid and polyvinylpyrrolidone (PVP) in sequence and stir thoroughly to obtain a homogeneous spinning solution. (2) Using electrospinning process, the homogeneous spinning solution is electrospun onto the roller of the roller collector to obtain the precursor nanofiber membrane; (3) The precursor nanofiber membrane is laid flat and pre-sintered at 200-300℃ to obtain a flat fiber sheet. Then the fiber sheet is sintered at 500-700℃ to obtain GDC nanofiber sheet. (4) Cut the GDC nanofiber sheet into several small pieces, stack these small pieces in a cross-fiber orientation and press them into a mold to obtain a blank; then sinter the blank after demolding at 500-700℃ to obtain a GDC solid electrolyte block with an oriented nanofiber stacking structure.
2. The method for preparing a GDC solid electrolyte bulk material with an oriented nanofiber stacking structure according to claim 1, characterized in that: In step (1), cerium source and gadolinium source are weighed according to a Gd doping molar fraction of 20%.
3. The method for preparing a GDC solid electrolyte bulk material with an oriented nanofiber stacking structure according to claim 1 or 2, characterized in that: In step (1), the cerium source is cerium oxide and the gadolinium source is gadolinium oxide.
4. The method for preparing a GDC solid electrolyte bulk material with an oriented nanofiber stacking structure according to claim 1, characterized in that: In step (1), the amount of organic solvent used is: 10-20 mL of organic solvent is added per gram of total mass based on the total mass of cerium source and gadolinium source.
5. The method for preparing a GDC solid electrolyte bulk material with an oriented nanofiber stacking structure according to claim 4, characterized in that: In step (1), the amount of organic solvent used is: based on the total mass of cerium source and gadolinium source, 13 to 15 mL of organic solvent is added per gram of total mass.
6. A method for preparing a GDC solid electrolyte bulk material with an oriented nanofiber stacking structure according to claim 4 or 5, characterized in that: The organic solvent is N,N-dimethylformamide (DMF).
7. A method for preparing a GDC solid electrolyte bulk material with an oriented nanofiber stacking structure according to claim 1 or 2, characterized in that: In step (1), the molar ratio of citric acid to the total amount of metal ions is (0.5-2):1, and the total amount of metal ions is the sum of the amounts of cerium ions and gadolinium ions.
8. The method for preparing a GDC solid electrolyte bulk material with an oriented nanofiber stacking structure according to claim 7, characterized in that: In step (1), the molar ratio of citric acid to the total amount of metal ions is (0.8 to 1.2):1, and the metal ions are the sum of cerium ions and gadolinium ions.
9. A method for preparing a GDC solid electrolyte bulk material with an oriented nanofiber stacking structure according to claim 1 or 2, characterized in that: In step (1), polyvinylpyrrolidone (PVP) with a weight-average molecular weight of 1 to 2 M is selected, and the amount of PVP added accounts for 8% to 15% of the total mass of the homogeneous spinning solution.
10. The method for preparing a GDC solid electrolyte bulk material with an oriented nanofiber stacking structure according to claim 9, characterized in that: In step (1), polyvinylpyrrolidone (PVP) with a weight-average molecular weight of 1.3M is selected, and the amount of PVP added accounts for 10% of the total mass of the homogeneous spinning solution.
11. The method for preparing a GDC solid electrolyte bulk material with an oriented nanofiber stacking structure according to claim 1, characterized in that: In step (2), the electrospinning process is as follows: the homogeneous spinning solution is transferred to the electrospinning device and collected by a roller collector. During the electrospinning process, the applied DC voltage is 10-20kV, the distance between the needle and the roller collector is 10-20cm, the spinning solution supply rate is 0.5-2.0mL / h, and the roller of the roller collector rotates at a speed of 1000-5000rpm. The roller collector is used to apply circumferential stretching and directional alignment to the deposited fibers to obtain the precursor nanofiber membrane.
12. The method for preparing a GDC solid electrolyte bulk material with an oriented nanofiber stacking structure according to claim 11, characterized in that: In step (2), before electrospinning, a release substrate is first laid on the surface of the roller collector; during the electrospinning process, the applied DC voltage is 14-16kV, the distance between the needle and the collector is 14-16cm, the spinning solution supply rate is 1.0-1.5mL / h, and the rotation speed of the roller collector is 2500-3500rpm.
13. A method for preparing a GDC solid electrolyte bulk material with an oriented nanofiber stacking structure according to claim 1, 2, 11, or 12, characterized in that: In step (3), after the precursor nanofiber membrane is laid flat, several breathable weights to prevent the fiber membrane from curling are placed at intervals on the surface of the precursor nanofiber membrane, and the membrane is treated at a temperature of 200-300°C for 4-8 hours in an air atmosphere to pre-sinter the precursor nanofiber membrane, so that the fiber membrane completes the initial degreasing and pre-oxidation shrinkage to obtain a flat fiber sheet. Next, the heavy object is removed, the fiber sheet is transferred to a flat firing plate, and a breathable plate is pressed on the surface of the fiber sheet. The temperature is raised to 500-700°C at a rate of 3-10°C / min and held for 30-120 minutes to completely decompose the residual organic matter and form the GDC fluorite phase. After cooling, brittle GDC nanofiber sheets are obtained.
14. The method for preparing a GDC solid electrolyte bulk material with an oriented nanofiber stacking structure according to claim 13, characterized in that: In step (3), the pre-sintering temperature in air atmosphere is 250℃ and the processing time is 6h; the final temperature of the fiber sheet after it is transferred to the sintering plate is 600℃, the heating rate is 3~10℃ / min, and the holding time is 60min.
15. A method for preparing a GDC solid electrolyte bulk material with an oriented nanofiber stacking structure according to claim 1 or 2, characterized in that: In step (4), the GDC nanofiber sheet is cut into several small pieces, and these small pieces are stacked in a pressing mold with the fiber orientation crossed. An axial pressure of 1 to 5 MPa is applied to the stacked sheet at room temperature to densify and embed the stacked sheet to obtain a blank. Next, the demolded blank is heated from room temperature to 500-700℃ at a heating rate of 3-10℃ / min and held for 20-60min for sintering strengthening to obtain a GDC solid electrolyte block with an oriented nanofiber stacking structure.
16. The method for preparing a GDC solid electrolyte bulk material with an oriented nanofiber stacking structure according to claim 15, characterized in that: In step (4), the axial pressure applied to the stacked sheets by the pressing mold when making the blank is 2 MPa; and after the blank is demolded, it is heated from room temperature to 600°C at a heating rate of 3 to 10°C / min and held at that temperature for 30 min for sintering strengthening.
17. A GDC solid electrolyte bulk, characterized in that: The GDC solid electrolyte block is a GDC solid electrolyte block with an oriented nanofiber stacking structure prepared by the preparation method described in any one of claims 1 to 16.
18. A low-temperature operating GDC-based oxygen sensor, characterized in that: include: GDC solid electrolyte bulk material, wherein the GDC solid electrolyte bulk material is prepared by the preparation method of any one of claims 1 to 16 and has an oriented nanofiber stacking structure, wherein the GDC solid electrolyte bulk material has an opposing upper surface and a lower surface; A first porous platinum electrode is disposed on the lower surface of the GDC solid electrolyte block; A second porous platinum electrode is disposed on the upper surface of the GDC solid electrolyte block; The first lead wire is used to lead out the potential signal of the first porous platinum electrode; The second lead wire is used to extract the potential signal of the second porous platinum electrode.
19. The cryogenic GDC-based oxygen sensor according to claim 18, characterized in that: include: A GDC solid electrolyte block having an oriented nanofiber stacking structure, the GDC solid electrolyte block having opposing upper and lower surfaces; A first porous platinum electrode is disposed on the lower surface of the GDC solid electrolyte block; A second porous platinum electrode is disposed on the upper surface of the GDC solid electrolyte block; The LSM internal reference block is disposed on the upper surface of the second porous platinum electrode; A platinum current collector layer is disposed on the upper surface of the LSM internal reference block; A glass sealing layer covers all sides of the GDC solid electrolyte block, all seams between the side of the GDC solid electrolyte block and the side of the second porous platinum electrode, all sides of the second porous platinum electrode, all seams between the side of the second porous platinum electrode and the side of the LSM internal reference block, and all sides of the LSM internal reference block. The sealed reference cavity is formed by the GDC solid electrolyte block, the LSM internal reference block, and the glass sealing layer, and the second porous platinum electrode is located inside the sealed reference cavity; The first lead wire is connected to the first porous platinum electrode through conductive silver paste and is used to extract the potential signal of the first porous platinum electrode. The second lead wire is connected to the platinum current collector layer via conductive silver paste and is used to extract the potential signal of the second porous platinum electrode.
20. The cryogenic GDC-based oxygen sensor according to claim 19, characterized in that: The preparation method of LSM internal reference bulk is as follows: weigh a predetermined amount of LSM powder and place it in a tableting mold, press it into shape under a pressure of 1-5 MPa, and sinter the shaped body at 1300-1500℃ for 8-12 hours to complete solid-state sintering and obtain a dense LSM internal reference bulk.
21. The cryogenic GDC-based oxygen sensor according to claim 19 or 20, characterized in that: The first porous platinum electrode is formed by sintering and solidifying a porous platinum electrode slurry coated on the lower surface of the GDC solid electrolyte block at 850-900℃. The second porous platinum electrode is formed by sintering and curing a porous platinum electrode slurry that bonds the upper surface of the GDC solid electrolyte block to the lower surface of the LSM internal reference block at 850-900℃. The platinum current collector layer is formed by sintering and curing a porous platinum electrode paste coated on the upper surface of the LSM internal reference block at 850–900℃. The glass sealing layer is formed by coating a glass slurry made of low-melting-point glass powder and organic solvent, which is then melted at 800-900℃ and cooled to solidify.